ANALISIS AKUNTANSI PEMBIAYAAN GADAI EMAS BERDASARKAN PSAK 107 (STUDI KASUS PADA BANK SYARIAH MANDIRI CABANG BANDA ACEH) - Sari, Ayu Ramadhana; Arfan, Muhammad (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
This study aimed to find out the accounting treatment of Islamic gold pawn that implemented by Syariah Mandiri Bank in Banda Aceh and to find out how the Statement of Financial Accounting Standard (PSAK) No. 107 about ijarah has been implemented. The research method used in this study is descriptive qualitative, with primary data source. The author collected the data by interviewing the head of pawn division of Syariah Mandiri Bank in Banda Aceh and used the data obtained as guidelines of ijarah accounting treatment that applied to the sharia gold pawn financing product. The results of this study found that overall Syariah Mandiri Bank has applied and enacted PSAK 107 (ijarah), Fatwa of National Sharia Council ofIndonesia No.26/DSN-MUI/III/2002, SE BI No. 14/7/DPbs dated 29 February 2012 and Civil Code article 2150 /d 1161 on pawn.